If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-2)/2=6(x+3)/12
We move all terms to the left:
6(x-2)/2-(6(x+3)/12)=0
We calculate fractions
6x/()+(-(6(x+3)*2)/()=0
We calculate terms in parentheses: +(-(6(x+3)*2)/(), so:We get rid of parentheses
-(6(x+3)*2)/(
We multiply all the terms by the denominator
-(6(x+3)*2)
We calculate terms in parentheses: -(6(x+3)*2), so:We get rid of parentheses
6(x+3)*2
We multiply parentheses
12x+36
Back to the equation:
-(12x+36)
-12x-36
Back to the equation:
+(-12x-36)
6x/()-12x-36=0
We multiply all the terms by the denominator
6x-12x*()-36*()=0
We add all the numbers together, and all the variables
6x-12x*()=0
| 75–3.5y–4y=4y+6= | | 5x-5=3x-1+x | | 1=0.3x-0.6-23 | | -13+x=5x | | 3x-2x-1=2 | | 5.4b+14=22 | | S=2·3.14h | | 4.6+10m=7.12 | | 30x+10x-30=10 | | -3x-2-1x=2 | | 3(x-1)-4=4=3x-7 | | 5x-10=2(x-8)+6 | | 5y+y-6=8(y+8) | | -7=3f+7 | | 3.44n+(4.38*4n)=62.88 | | 3(-n-4)=-30 | | 12+w(2)=7w | | -5x+12=51 | | 65-9x=-15x+67 | | 3.44n+4.384n=62.88 | | 178=-3+4(-6x+4) | | 1x-1=x+7 | | 8(x-3)-9=33 | | 11x+3=10x-6 | | 3.44n+4.38*4n=62.88 | | 8-2b=-2{b=-3;b=0;b=5 | | 3n-7n=6n-2n | | 3x-17=7x+47 | | -2+23x=42 | | -2(3x-14)+4=30-3 | | 5x^2−4x−7=1−x. | | 4c-1=6c+5 |